Toward exploring a new path for parenting within a digital environment: an investigation of Korean fathers’ online involvement in parenting - Kim, Juhu; Jeon, Yooyoung; Kwak, Seungju (European Early Childhood Education Research Journal, 2023)
The purpose of this study was to investigate fathers’ online involvement in parenting focusing on the process of promoting and supporting children’s lives using computers or smart devices. For this purpose, 411 Korean fathers raising young children participated in a survey. The results showed a marginally low level of online involvement in parenting. Among the five sub-constructs of fathers’ online involvement in parenting, the highest and lowest mean scores were found in ‘sharing responsibility’ and ‘educational involvement’ respectively. Concerning group differences in fathers’ online involvement in parenting, only education and income showed statistically significant differences. Specifically, the fathers with higher levels of education and income showed more active online involvement in parenting. A cluster analysis was conducted to determine whether fathers’ groups showed distinct patterns of online involvement. The results revealed four definable groups: ‘low involvement’, ‘easy-task involvement’, ‘active involvement’, and ‘spousal communication’. Implications for policy development facilitating fathers’ online involvement in parenting were discussed.
Keywords: child-rearing; Father parenting; online involvement; smart devices